ANALISIS HADIST TARBAWY TENTANG SIFAT KEPRIBADIAN PENDIDIK (HADIST KONTEMPORER) - Septina Laylatu Zahro; NURUL HIDAYAH (Al-Lahjah, 2021)
Abstract Personality is a description of attitudes that differ from one individual to another. This is due to the adjustment of views in a dynamic context related to integrated behavior and which describes the interaction between inherited abilities and environmental influences. Education is the process of changing the attitudes and behavior of a person or group of people in an effort to mature humans through teaching and training efforts, also means the process, method, act of educating students. Based on the study and analysis in the hadith used as a reference for the study, it was concluded that being an educator must have good personality traits. The position of an educator as a parent of students in the school environment, there are several traits possessed by an educator, namely having a gentle nature, compassion, speaking and being honest so that students can imitate, an educator has a desire to return his knowledge to Allah swt, and pay attention to the condition of the students. In addition, an educator must also pay attention to the requirements that must be possessed by an educator, namely must be fair to his students by not discriminating each other, be tolerant with all kinds of attitudes, an educator must be sincere with educating his students. Keywords: Personality traits of educators, hadith, education